Reconstructing Our Orders Artificial Intelligence and Human Society - Jin, Donghan (Springer Nature Singapore : Imprint: Springer, 2018)
This book discusses in detail the great historical and social significance of the development of Artificial Intelligence (AI). It consists of seven chapters, each focusing on a specific issue related to AI, such as ethical principles, legal regulations, education, employment and security. Adopting a multidisciplinary approach, it appeals to wide readership, ranging from experts and government officials to the general public.